Prevalence of cardiovascular risk factors in long-term survivors of childhood cancer: 16 years follow up from a prospective registry. (June 2015) - Felicetti, Francesco; D'Ascenzo, Fabrizio; Moretti, Claudio; Corrias, Andrea; Omedè, Pierluigi; Marra, Walter Grosso; Arvat, Emanuela; Fagioli, Franca; Brignardello, Enrico; Gaita, Fiorenzo
Background: Childhood cancer survivors (CCSs) have an increased risk of overweight and dyslipidaemia, but the distribution and the potential relationships between anticancer therapies and cardiovascular risk factors have been heterogeneously and not prospectively described. Methods: All consecutive CCSs with primary cancer diagnosed between 1973–2007 and subsequently referred to our outpatient clinic were enrolled. Hypercholesterolaemia (total cholesterol >200 and/or low density lipoprotein (LDL)>160 mg/dl) was the primary end point, hypertriglyceridaemia (triglycerides >200 mg/dl) and body mass index >30 kg/m 2 the secondary end points. Cox multivariate adjustments were performed to account for differences in cancer and treatments. Results: A total of 340 patients were included (197 male, 143 female; mean age at last follow-up 24.1 ± 3.2). The most common diagnosis were haematological malignancies ( n  = 227) and brain tumours ( n  = 51). After a median follow-up of 16.1 years, hypercholesterolaemia was diagnosed in 67 CCSs (20%), hypertriglyceridaemia in 20 CCSs (6%) and obesity in 28 CCSs (8%). Total body irradiation and growth hormone deficiency increased the risk of both hypercholesterolaemia (hazard ratio (HR) = 2.7; confidence interval (CI) 1.2–4.4 and HR = 2.3; CI 1.1–4.9; all p  < 0.05) and hypertriglyceridaemia (HR = 6.5; CI 1.4–31 and HR = 7.2; CI 1.1–43; all p  < 0.05). The risk of hypercholesterolaemia was also higher in CCSs who underwent autologous haematopoietic stem cell transplantation (HR = 3.2; CI 1.7–5.9; p  < 0.001) or platinum-based chemotherapy (HR = 2.7; CI 1.5–4.9; p  < 0.001), whereas a previous diagnosis of brain tumour (HR = 10; CI 1.2–45; p  < 0.05) and anthracyclines exposure (HR = 1.3; CI 1.2–26; p  < 0.05) significantly predicted obesity. Conclusion: CCSs show a high and variable risk for developing dyslipidaemia and obesity, depending on cancer diagnosis and treatments. Therefore, they need accurate and tailored control of their cardiovascular risk profile.